Customs Payments Analysis as an Object of Economic Activity of Customs Authorities: Modern Realities of Shadow Exports - S. V. Pankova; V. S. Levin; V. V. Popov (Учёт. Анализ. Аудит)
The search for reserves for stabilization of Russian economy is coming to the fore in the context of the ongoing crisis. Given its raw material orientation, a significant share of which is accounted for by exports, and the high share of customs payments (in particular, export customs duties on oil and gas) in the structure of the Federal budget, it is extremely important to assess the estimated losses of customs payments as a result of shadow exports, which determines the relevance of this study. The paper discribes assessing the volume of customs payments in the conditions of the country’s shadow economy development as well as searching for sources of their increase in the structure of Federal budget revenues due to organizational measures. A review of positions of the Russian scientists in the field of economic categories including taking into account the normative and reference documentation. In this study it is proved that the activities of customs authorities belong to the type of organizational and economic relations and customs payments are an economic category. A methodological tool for economic analysis has been developed to identify the significance of losses from shadow exports for the state budget as well as to assess the correctness of the distribution of import customs duties to the budgets of the EAEU member States. The theoretical and practical significance of the study is determined by the prospects for increasing the volume of the Federal budget revenue due to the collection of customs duties. The study may be interesting for government agencies of foreign trade policy and Federal budget formation.